2015
DOI: 10.1039/c5dt02822a
|View full text |Cite
|
Sign up to set email alerts
|

Four-coordinate nickel(ii) and copper(ii) complex based ONO tridentate Schiff base ligands: synthesis, molecular structure, electrochemical, linear and nonlinear properties, and computational study

Abstract: We report the synthesis, characterization, crystal structures, nonlinear-optical (NLO) properties, and density functional theory (DFT) calculations of nickel(ii) and copper(ii) complex based ONO tridentate Schiff base ligands: two mononuclear compounds, [Ni(An-ONO)(NC5H5)] (5) and [Cu(An-ONO)(4-NC5H4C(CH3)3)] (6), and two heterobimetallic species, [M(Fc-ONO)(NC5H5)] (M = Ni, 7; Cu, 8), where An-ONOH2 (3) and Fc-ONOH2 (4) are the 1 : 1 condensation products of 2-aminophenol and p-anisoylacetone and ferrocenoyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 122 publications
5
49
0
Order By: Relevance
“…Ferrocenes such as the seminal example of cis ‐1‐ferrocenyl‐2‐(4‐nitrophenyl)ethylene (Figure , left) were found by Green's group, followed by other groups, to show nonlinear optical (NLO) properties, with applications in optical signal processing such as the frequency doubling of laser light.…”
Section: Ferrocenes In Supramolecular Ensembles Liquid Crystals Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrocenes such as the seminal example of cis ‐1‐ferrocenyl‐2‐(4‐nitrophenyl)ethylene (Figure , left) were found by Green's group, followed by other groups, to show nonlinear optical (NLO) properties, with applications in optical signal processing such as the frequency doubling of laser light.…”
Section: Ferrocenes In Supramolecular Ensembles Liquid Crystals Andmentioning
confidence: 99%
“…It turned out that both the reduction reactions and the organic connectors had a significant influence on the 4,4′‐bipyridinium system . The groups of Hamon, Saillard, Carrillo, Manzur, and Ledoux‐Rak developed another remarkable series of molecular systems in which ferrocene is conjugated with Schiff bases; excellent NLO properties were disclosed . The largest quadratic hyperpolarizability value (970 × 10 –30 esu) was determined for palladium‐containing dimetallic ferrocene Schiff‐base species .…”
Section: Ferrocenes In Supramolecular Ensembles Liquid Crystals Andmentioning
confidence: 99%
“…This proligand is soluble in the common organic solvents except diethyl ether and hydrocarbons. The neutral mononuclear pentacoordinate chloro-iron(III) complex 3 was synthesized following a known one-pot two-step procedure [32]. First, the diprotic derivative 2 was doubly deprotonated with potassium tert-butoxide in THF at ambient temperature, before addition of a THF solution of anhydrous iron(III) chloride (Scheme 2).…”
Section: Synthesesmentioning
confidence: 99%
“…The mononuclear (1, 2) and bimetallic (3, 4) complexes were readily prepared by reacting the known tridentate Schiff-base ligand precursors R-C(O)CH=C(CH3)NH-C6H4-2-OH (R = anisyl (L1), ferrocenyl(L2)) 18 with one equiv. of hydrated M(II) nitrate salt (M = Ni, Cu), and a slight excess of the electro-active pyridyl 2,6-diphenylmethylenepyran (PyMP), under basic conditions in THF for 12 h at room temperature (see Experimental for details and Scheme 1).…”
Section: Synthesis and Characterization Of Complexesmentioning
confidence: 99%
“…These four-coordinate Ni(II) and Cu (II) chromophores displayed good second-order NLO polarizabilities, with β values ranging from 170-350 x 10 -30 esu (HRS with 1.91 μm incident wavelength). 18 In a more recent paper, we showed that the [(R-ONO)M] units can be used as building blocks for the construction of expanded and more complex architectures such as dimers and coordination polymers, taking advantage of the lability of the pyridine ancillary ligand. 19 On the other hand, electrochemical studies have shown that the organic chromophores ferrocenyl-, [20][21][22][23] pyridyl-, 21 and phenylmethylenepyrans 24 can undergo fast dimerization through C-C σ-bond making upon oxidation, and that the resulting bispyrylium species are irreversibly reduced back to the initial methylenepyran by C-C bond breaking.…”
Section: Introductionmentioning
confidence: 99%